All‐cause and liver‐related mortality risk factors in excessive drinkers: Analysis of data from the UK biobank. (19th November 2022) - Whitfield, John B.; Seth, Devanshi; Morgan, Timothy R.; ,
Abstract: Background: High alcohol intake is associated with increased mortality. We aimed to identify factors affecting mortality in people drinking extreme amounts of alcohol. Methods: We obtained information from the UK Biobank on approximately 500, 000 participants aged 40–70 years at baseline assessment in 2006–2010. Habitual alcohol intake, lifestyle and physiological data, laboratory test results, and hospital diagnoses and death certificate data (to June 2020) for 5136 men (2.20% of male participants) and 1504 women (0.60%) who reported consuming ≥80 or ≥50 g/day, respectively, were used in survival analysis. Results: Mortality hazard ratios for these excessive drinkers, compared to all other participants, were 2.02 (95% CI 1.89–2.17) for all causes, 1.89 (1.69–2.12) for any cancer, 1.87 (1.61–2.17) for any circulatory disease, and 9.40 (7.00–12.64) for any liver disease. Liver disease diagnosis or abnormal liver function tests predicted not only deaths attributed to liver disease but also those from cancers or circulatory diseases. Mortality among excessive drinkers was also associated with quantitative alcohol intake; diagnosed alcohol dependence, harmful use, or withdrawal syndrome; and current smoking at assessment. Conclusions: People with chronic excessive alcohol intake experience decreased average survival, but there is substantial variation in their mortality, with liver abnormality and alcohol dependence or other alcohol use disorders associated with a worse prognosis. Clinically, patients with these risk factors and high alcohol intake should be considered for early or intensive management. Research can usefully focus on the factors predisposing to dependence or liver abnormality. Abstract : High alcohol intake increases mortality but little is known about risk factors which affect mortality in high‐risk drinkers. We assessed 6640 UKB participants reporting >80g/50g (men/women) alcohol per day. Alcohol use disorders, diagnosis of liver disease, abnormal liver function tests and erythrocyte morphology predicted higher risk of death overall, and from liver disease, cancers or cardiovascular diseases. Mortality Hazard Ratios, compared to all other participants, were 2‐fold for all causes, cancers, circulatory diseases, and >9‐fold for any liver disease.